2013
DOI: 10.5424/fs/2013222-02953
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of Decision Support Systems in participatory forest planning: a comparison between Finland and Italy

Abstract: Aim of study: Participation of stakeholders is considered an essential element in producing, at different spatial and temporal scales, forest plans accepted by local community and fulfilling the requirements of Sustainable Forest Management. Increasingly, computer-based decision support systems (DSS) and tools are being introduced to assist stakeholders and decision-makers in coping with the complexities inherent in participatory forest planning. The study aimed to investigate how useful the users and research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Our results showed that the use of DSSs during the Intelligence phase is critical, as confirmed by previous reports (Raggad 1996, De Meo et al 2013). According to respondents, Intelligence seems the step with the lesser usefulness for DSSs.…”
Section: Dss Usefulness In Participatory Forest Planningsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results showed that the use of DSSs during the Intelligence phase is critical, as confirmed by previous reports (Raggad 1996, De Meo et al 2013). According to respondents, Intelligence seems the step with the lesser usefulness for DSSs.…”
Section: Dss Usefulness In Participatory Forest Planningsupporting
confidence: 80%
“…The present study has a dual purpose. Firstly, it will extend the research of De Meo et al (2013) to a wider geographical area. Secondly, it will focus not only on analyzing final users' point of view on the Usefulness of DSSs in participatory forest planning, but also on the Perceived Usefulness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the way the methods are applied may actually be a more relevant factor than which methods are applied (see also De Meo et al 2013).…”
Section: Recommendations For Mixing Methodsmentioning
confidence: 98%
“…Similarly, the implementation of scenario-based solutions (i.e., models and tools) at the operational scale for maximizing FES provision in forest management planning contexts is still lacking in many parts of Italy. Although several studies have attempted to combine decision support systems with participatory processes (Basilicata region; [26]) and addressed the multi-functionality of forest landscapes (Molise region; [27]), many more efforts are still needed to consider FES in a spatially-explicit way and their related trade-offs in forest management planning in Italy.…”
Section: Introductionmentioning
confidence: 99%